2008
DOI: 10.1007/s11033-008-9415-0
|View full text |Cite
|
Sign up to set email alerts
|

Fas expression on peripheral blood lymphocytes in systemic lupus erythematosus: relation to the organ damage and lymphocytes apoptosis

Abstract: Systemic lupus erythematosus (SLE) is a common autoimmune disease with complex etiology. Recently, a possible role of apoptotic cells in its pathogenesis has been suggested. This study is to evaluate the expression of Fas antigen on peripheral blood lymphocytes (PBLs) in SLE, to determine whether membrane Fas (mFas) has a role in the organ damage in SLE and to explore its relationship with the early apoptosis of the PBLs in SLE. Flow cytometry was used to evaluate the expression of mFas on PBLs in 68 Chinese S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…To our knowledge, no biomarkers apart from lymphocyte Fas expression, 14 sFas, 12 CRP 13 , and osteopontin 15 have been shown to associate with organ damage as defined by SDI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, no biomarkers apart from lymphocyte Fas expression, 14 sFas, 12 CRP 13 , and osteopontin 15 have been shown to associate with organ damage as defined by SDI.…”
Section: Discussionmentioning
confidence: 86%
“…apoptosis stimulating fragment (Fas/CD95), both membrane bound and soluble (sFas), CRP and osteopontin), and organ damage. [12][13][14][15] However, only plasma levels of osteopontin have been shown predict organ damage, and this was shown for a relatively small study group of SLE patients. 15 Soluble urokinase plasminogen activator receptor (suPAR) is part of the plasminogen activation system and is involved in inflammation, tissue remodeling and cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Fas is an apoptosis-promoting cell surface receptor, and interactions between Fas and FasL play an essential role in maintaining immune homeostasis [35]. Fas expression on total peripheral blood lymphocytes has been reported to be higher in SLE patients than in HCs [11, 36, 37] and to correlate with both disease activity [11, 36]and organ damage [37]. Similarly, Amasaki et al reported higher mean fluorescence intensity due to Fas expression on both CD4 + and CD8 + T cell subsets in patients than in HCs [38].…”
Section: Discussionmentioning
confidence: 99%
“…CD25? T lymphocytes [58,59], high B-cell chemoattractant of CXC chemokine (CXCL13) production [60,61] and defective Fas expression [62,63]. The main neuromuscular side effect of antimalarials is a marked neuromyopathy, characterized by slowly progressive weakness of insidious onset.…”
Section: Discussionmentioning
confidence: 99%